The prognostic value of systemic immune-inflammation index in surgical esophageal cancer patients: An updated meta-analysis - Li, Xiaoqu; Zhang, Shuhao; Lu, Juan; Li, Chao; Li, Naibin (Frontiers in Surgery, 2022)
Purpose To identify the prognostic role of systemic immune-inflammation index (SII) in esophageal cancer patients receiving operation. Methods The PubMed, EMBASE, Web of Science, Cochrane Library, WanFang and CNKI electronic databases were searched up to February 17, 2022 for relevant studies. The hazard ratios (HRs) and 95% confidence intervals (CIs) were combined to assess the association between SII and prognosis in surgical esophageal cancer patients. The primary outcome was overall survival (OS) and secondary outcomes were progression-free survival (PFS) and cancer-specific survival (CSS). All statistical analyses were conducted by STATA 15.0 software. Results A total of nine retrospective studies involving 3565 participates were included. The pooled results indicated that high SII was significantly related with poor OS (HR=1.58, 95% CI: 1.23-2.02, P＜0.001). However, subgroup analysis based on pathological type demonstrated that high SII was an independent predictor for poor OS only in esophageal squamous cell carcinoma (ESCC) patients (HR=1.72, 95% CI: 1.34-2.21, P＜0.001). Besides, SII was also significantly associated with poor PFS (HR=1.94, 95% CI: 1.61-2.35, P＜0.001) and CSS (HR=1.44, 95% CI: 1.04-1.99, P=0.027) in ESCC patients. Conclusion The SII could serve as an independent prognostic factor in surgical ESCC patients and higher SII was related with worse survival. However, more prospective high-quality studies are still needed to verify above findings.